2017
DOI: 10.1002/ep.12643
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of a solar‐assisted infrared timber drying system

Abstract: This study investigates convective‐infrared drying characteristics of timber. The biggest disadvantage of infrared heating systems is the uncontrollable rise of the surface temperature up to extremely high values, which causes damage to the product. In this study, the power of an infrared system was controlled and adjusted according to the surface temperature of the product. In doing so, the surface temperature of the infrared heater was prevented from reaching up to values that could damage the product. Durin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 16 publications
0
10
0
3
Order By: Relevance
“…Similar result was obtained by Doymaz, Karasu, and Baslar (), who found that phenolics were degraded during infrared heating of jujube fruit at 88 W infrared power. This result occurred because infrared treatment could heat the material to a very high temperature (Aktaş et al, ). It was also found that the UN‐treated sample presented the lowest phenolic content of 38.16 ± 1.44 mg GA/g d.b..…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar result was obtained by Doymaz, Karasu, and Baslar (), who found that phenolics were degraded during infrared heating of jujube fruit at 88 W infrared power. This result occurred because infrared treatment could heat the material to a very high temperature (Aktaş et al, ). It was also found that the UN‐treated sample presented the lowest phenolic content of 38.16 ± 1.44 mg GA/g d.b..…”
Section: Resultsmentioning
confidence: 99%
“…However, IB is only applicable to thin materials such as petals because the very limited penetration depth (Ginzburg, ; Nindo, Kudo, & Bekki, ). The biggest disadvantage of infrared heating is the uncontrollable rise of the temperature up to a extremely high value, which leads to an adverse effect on product quality (Aktaş, Ceylan, Ergün, Gürel, & Atar, ). To solve this problem, intermittent infrared heating achieved by keeping product temperature constant through turning the energy supply on and off, was proposed in previous studies (Chua & Chou, ; Sandu, ).…”
Section: Introductionmentioning
confidence: 99%
“…The best result in terms of drying chamber temperature was found with gravel floor having black paint. Convective‐infrared drying characteristics of timber has been done by Mustafa et al 5 Shiva et al 6 discussed about different solar PV technologies, which decrease fuel dependency. It was also concluded that developments in agricultural techniques with PV would be greatly advantageous.…”
Section: Introductionmentioning
confidence: 99%
“…From the survey of the literature, it can be resolved that a basic technique for rating the thermal mechanism of different type of solar dryers has not been developed because of the complexity of the solar dryer system. It includes gradual heat and mass transfer circumstance …”
Section: Introductionmentioning
confidence: 99%